Itineraries of Lutheranism in Santa Catarina and Paraná - Haroldo Baade, Joel (Vox Scripturae - Revista Teológica Internacional, 2025)
This article is an analysis of the formation of the Sínodo Evangélico Luterano Unido (SELU) [United Lutheran Evangelical Synod], in 1962, stemming from the fusion of the Lutheran Church in Brazil (1905) and the Evangelical Synod of Santa Catarina and Paraná (1911), normally called synods. The trajectories of these two institutions were marked in good measure by mutual combat, being that the origins of these conflicts are in the pre-existing congregational divergences as well as in theological and confessional differences which remit back to the history of the institutions as well as to the origins of the pastors and members who make up the two synods. The research consisted in a historiographic analysis of qualitative character, making use of primary sources coming from the archives of the ecclesial communities belonging to the institutions studied and from the historical archives of the IECLB in São Leopoldo, RS; secondary sources; and oral sources. Interviews were carried out with religious ministers of the two institutions which experienced the fusion in 1962. The relevance of the study resides in its unprecedented character, contributing to the comprehension of the constitution of the cultural patrimony of the states of Santa Catarina and Paraná, which are covered by the two institutions here studied. The nationalisms of the end of the 19th century and the first half of the 20th century determined the history of the synods. Mainly with the result of the Second World War, the ideal of edifying the Church based on an ethnic matrix was revealed as invalid leading the synods to continue the dialog that had begun under their condition of Germanity, however now with a new discourse, marked by a theological reorientation. This new order gained formal expression with the constitution of the Federação Sinodal (FS) [Synod Federation]/ Igreja Evangélica de Confissão Luterana no Brasil (IECLB) [Evangelical Church of Lutheran Confession in Brazil], in 1949. From the commitment with the new established order there arose the need for restructuring the two synods, which had experienced a parallel development even though co-existing in the same territory. The constitution of the SELU is a fundamental marking point in the consolidation of the church of Lutheran confession in Brazil.